Hepatitis B and C Prevalence and Prevention Awareness among Health Care Workers in a Tertiary Care Hospital - Hussain, Shagufta; Patrick, Niveen Asher; Shams, Rabia (International Journal of Pathology, 2018)
Objective: To find the prevalence of Hepatitis B and C and to assess the current Hepatitis B vaccination statusand knowledge of standard prophylaxis against blood borne infections in selected group of health care workers atPakistan Institute of Medical Sciences (PIMS) Islamabad.Study Settings: Descriptive cross sectional prospective study.Place and Duration: Between 15th June 2009–30th June 2009.Infection Control Committee in collaboration with Microbiology Department, Pakistan Institute of Medical SciencesIslamabad.Materials and Methods: Three hundred eighty three health workers comprising of nurses and Lab workers wereinterviewed after taking verbal consent using a self administered questionnaire. Data was analyzed using SPSSversion 13.Results: Among the 383 HCWs interviewed nurses were 72% (277) and Lab workers were 27.5 %( 106) .Thereage ranged from17-59 years with mean age of 34.38 years. 41% of health care workers had service lengthbetween 1-5 years. 57.6 %( 221) were completely vaccinated, 18.3 %( 70) partially vaccinated and 24 %( 92) werenot vaccinated at all. Awareness and attitude problem was identified as the main factor responsible for lack ofvaccination. 53.5% (206) had been exposed to needle stick injury at least 1-5 times in their whole professional life.48.1% (99) of the needle stick injury exposed personnel were aware of post exposure prophylaxis whereas 51.9%( 107) of them were ignorant of standard prophylaxis.Most of the individuals knew their Hepatitis B and C status i.e. 93.7% (359) while 6.3 %( 24) had never gotthemselves tested for hepatitis B& C. Hepatitis B positive were 0.5 %( 2), while 1.6 %( 6) were Hepatitis C positiveamong 359 HCWs.Conclusion: Percentage of HCWs vaccinated was low and the main factor responsible was awareness andattitude problem. At the same time non- availability of vaccine by the employer had been identified as the secondmost important reason for non vaccination.Half of the studied group was not aware of the precise post exposure prophylaxis .The prevalence of Hepatitis Band C was low in this high risk group as compared to general population of the area.